Moderasi Beragama Dalam Perspektif Ilmu Perbandingan Agama - Akbar, Maulana Rizky; Novendri, Mochammad (CV. ITTC INDONESIA, 2026)
Religious moderation is an important concept in maintaining harmony in Indonesia's multicultural and pluralistic society. This study aims to analyze religious moderation from the perspective of comparative religion and explain its relevance in Indonesian social life. The study uses a qualitative method with a library research approach through a review of various books, scientific journals, and academic sources related to religious moderation and comparative religion. The results show that religious moderation is a perspective and practice of religion that emphasizes balance, tolerance, justice, and the rejection of extremism and radicalism. From the perspective of comparative religion, religious moderation is understood as an effort to understand religious diversity objectively and inclusively in order to create dialogue and harmony between religious communities. Comparative religion plays a crucial role in building mutual respect and reducing negative prejudice between religious communities through an academic and dialogical approach. This study also finds that religious moderation has very strong relevance in Indonesia, especially in facing the challenges of intolerance, radicalism, and the spread of hate speech in the digital era. Furthermore, education plays a strategic role in strengthening the values ​​of religious moderation through learning tolerance, digital literacy, and respect for diversity. Thus, religious moderation is a crucial foundation for creating a peaceful, harmonious, and civilized society amidst Indonesia's religious and cultural diversity.